The multi-dimensional approach to drug-induced states: A commentary on Bayne and Carter's "dimensions of consciousness and the psychedelic state". Issue 1 (19th April 2020) - Fortier-Davy, Martin; Millière, Raphaël
Abstract: Bayne and Carter argue that the mode of consciousness induced by psychedelic drugs does not fit squarely within the traditional account of modes as levels of consciousness, and favors instead a multi-dimensional account according to which modes of consciousness differ along several dimensions—none of which warrants a linear ordering of modes. We discuss the assumption that psychedelic drugs induce a single or paradigmatic mode of consciousness, as well as conceptual issues related to Bayne and Carter's main argument against the traditional account. Finally, we raise a set of questions about the individuation of dimensions selected to differentiate modes of consciousness that could be addressed in future discussions of the multi-dimensional account.